Document Management System (DMS) dalam Mendukung Kinerja Audit Internal Perusahaan: Analisis Literatur - Vicki Herdiawan; Agus Munandar (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Document Management System (DMS) is an application of information technology that plays an important role in electronic document management. This study aims to evaluate the effectiveness of DMS in supporting the company's internal audit performance. The research method used is a literature review and bibliometric analysis of relevant articles for the 2021-2024 period. The results showed that the Document Management System (DMS) significantly contributed to speeding up the company's internal audit process, improving data accuracy, and reducing the risk of losing important documents. The success of the Document Management System (DMS) implementation is strongly influenced by management support and technological readiness in the company. This research provides a positive impact that the Document Management System (DMS) affects the effectiveness of internal audit work, especially if supported by implementation policies and user training.